The Collected Poems of Robert Creeley : 1975?2005. (University of California Press, 2006)
This definitive collection showcases thirty years of work by one of the most significant American poets of the twentieth century, bringing together verse that originally appeared in eight acclaimed books of poetry ranging from Hello: A Journal (1978) to Life & Death (1998) and If I were writing this (2003). Robert Creeley, who was involved with the publication of this volume before his death in 2005, helped define an emerging counter-tradition to the prevailing literary establishment--the new postwar poetry originating with Ezra Pound, William Carlos Williams, and Louis Zukofsky and expanding t.